Hubungan Penggunaan Rekam Medis Elektronik Dengan Kepuasan Pengguna Rekam Medis Elektronik Di Unit Rawat Jalan Rumah Sakit Umum Mitra Medika Amplas Medan Tahun 2022 - Sapriadi Sapriadi; Shinta Polmidar Romiani Lase (Jurnal Kesehatan dan Fisioterapi, 2023)
Background; Electronic Medical Record is the use of electronic methods for collecting, storing, processing, and accessing patient medical records in hospitals that have been stored in a multimedia database management system that collects various sources of medical data. Objective; this study was to determine the relationship between the use of electronic medical records and satisfaction with the use of electronic medical records in the Outpatient Unit of Mitra Medika Amplas General Hospital Medan in 2022. Method; The type of research used is quantitative which is an analytic survey with a cross-sectional approach. The sample in this study was 82 people consisting of 43 polyclinic doctors, 19 nurses, 18 registration staff, and 4 midwives. The data collection instrument used was a questionnaire which was distributed directly to the respondents. The data analysis used was univariate and bivariate analysis using the chi-square test. Results; In this study, it was found that out of 82 respondents, the majority used electronic medical records in the good category, namely 44 people (53.7%) and 41 people (50.0%) were satisfied. Based on the results of the chi-square test, there is a significant relationship between the variable use of electronic medical records and the satisfaction of electronic medical record users in the outpatient unit at RSU Mitra Medika Amplas in 2022 (p-value 0.018 < α 0.05). Conclusion; In this study, there is a significant relationship between the use of electronic medical records and the satisfaction of electronic medical record users in the outpatient unit of RSU Mitra Medika Amplas in 2022.Keywords: Electronic Medical Record, Satisfaction